Bioinformatics Analysis Uncovers the Importance of RTK-RAS-PI3K/Akt Regulation by Borneol in Overcoming Breast Cancer Resistance to Tamoxifen - Ali, Zulfikar; Hermawan, Adam (Indonesian Journal of Pharmacy, 2022)
Currently, tamoxifen-based hormonal treatment remains the first line for luminal A (estrogen receptor [ER]-positive) subtype breast cancer, with a response of more than 30%. Chemoresistance was induced by the long-term use of tamoxifen therapy. Therefore, to prevent resistance and improve the effectiveness of tamoxifen, combined therapy is required. This study used bioinformatics to identify possible borneol target genes and their mechanism for overcoming tamoxifen resistance in breast cancer cells. We used data from the gene expression omnibus (GEO) collection to find differentially expressed genes (DEGs). The Database for Annotation, Visualization, and Integrated Discovery (DAVID) site, version 6.8, was also used to undertake gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analysis of the DEGs. The STRING-DB site, version 11.0, was used to predict protein-protein interaction (PPI) study. The PPI analysis findings were visualized using the Cytoscape software, version 3.8.2. The hub gene was further calculated using the CytoHubba plugin. The genomic alterations from the hub gene were evaluated using cBioPortal, version 1.18.1. The potential target genes (PTGs) of borneol compounds are ESR1, FGFR2, STAT3, ERBB4, PRKCA, and RTK-RAS PI3K-Akt signaling as its prospective mechanism to overcome tamoxifen resistance in breast cancer cells. More studies are needed to confirm the potential of borneol to overcome tamoxifen resistance in breast cancer.